Organizational Decision Support Systems - Garrido, Paulo (2009)
This paper presents a notion for developing Organizational Decision Support Systems (ODSS). The lens used is to see ODSS as a specialization of Social Decision Support Systems (SDSS) and a generalization of Group Decision Support Systems (GDSS). A unit decision process can be raised by any person in a organizational whole, the organization itself or some sub-organization. The decision process can use a given formalism coherent with the idea that as the contributions from people in the decision process expands, so does the space of available perceptions (P), the space of available actions (A), strategies (S), and options (O), the space of available criteria (C) of valuation of options (V), leading to decision. Atomic decision processes link in the global decision process of the organization. Potential benefits, shortcomings and needed technologies are indicated as well as prospects of development.